E-Business: A Management Perspective - Jonathan Reynolds (New York Oxford University Press, 2010)
This text seeks to draw together a varied range of conceptual models and frameworks, existing empirical research, statistical and case study material to provide a coherent insight into e-business from a management perspective. It: - defines the nature and scope of e-business technologies and the brief history of their development and implementation, - reviews the environmental drivers facilitating and constraining the application and growth of e-business technologies - evaluates the ways in which e-business technologies can be applied within firms to achieve new business development and process improvements - considers the organisational dimension of e-business implementation within firms, from project management, skills and cultural perspectives - reflects upon the likely nature of future challenges and opportunities of e-business technologies Utilising extensive up to date examples and case studies throughout, such as eBay, Googlewhacking & Skype, this text primarily focuses on the contribution of e-business technologies to the effectiveness and efficiency of for-profit firms, with insights drawn, where relevant, on not-for-profit and public sector organisations. It includes the application of e-business technologies to both large and small firms in both developed and emerging economies. It extends beyond PC-based web channels to mobile and other platforms, including store-based kiosks and emerging, pervasive technologies, such as digital TV, SMS, m-commerce, PDAs and other location-based services. Online Resource Centre Lecturer Resources Case study bank Additional Exercises and Questions with solutions Powerpoint Slides Student resources Oxford NewNow End of Chapter answers Annotated Web Links Chapter summaries Flashcard Glossary Author Blog
Keywords: Business; Management; E-business; Global Digital Business (BIN2042-N)